DEVELOPING CHILDREN'S CREATIVITY THROUGH MANUFACTURING ECOBRICS FROM INORGANIC WASTE - Khulusinniyah, Khulusinniyah; Hakimah, Nur; Anam, Ahmad Choirul (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Children's creativity must be encouraged from a young age in order for them to reach their full potential. There are several techniques to encourage children's creativity; one of them is to create eco-bricks. This exercise will educate youngsters how to recycle trash and create new objects based on their imaginations. The preceding research makes use of classroom action research, which is conducted in four stages: preparation, implementation, observation, and reflection. This implementation resulted in an increase in children's creativity from 40% pre-cycle to 65% in cycle one, which increased to 85% in cycle two.